PENGARUH MEDIA GAME EDUKASI QUIZWHIZZER TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN IPAS MATERI GAYA DI SEKITAR KITA KELAS IV SD ISLAM AL-QUDS SAMARINDA TAHUN PEMBELAJARAN 2024/2025 - Monita, Tiara; Hidayat, Taufik; Makmun; Supriyatna, Yana; mMuhlis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Quizwhizzer educational game media on the learning outcomes of fourth-grade students at SD Islam Al-Quds Samarinda in the IPAS subject. This research is motivated by the low learning outcomes of students in the IPAS subject, which is caused by a lack of variation in learning methods and the use of technology. This study uses a Pre-Experimental method with a One-Group Pretest-Posttest Design. The sampling technique used is purposive sampling. Data were collected through interviews, learning outcome tests (pretest-treatment-posttest), and student response questionnaires. Data analysis was performed by testing the validity and reliability of the instruments, learning outcome tests, t-tests, and analysis of student responses. The results showed a significant increase in student learning outcomes, with an average pretest score of 54.33 increasing to 82 on the posttest, and an average N-Gain of 0.58 (medium category). The t-test showed t-count = 10.450 > t-table = 1.714, which proves that there is a significant influence. Student responses to the use of Quizwhizzer were also very positive, with an average score of 87.24 (very high category). Based on these research results, it can be concluded that there is an influence of the Quizwhizzer educational game media on the learning outcomes of students in the IPAS subject matter "Forces Around Us" in class IV SD Islam Al-Quds Samarinda. This study suggests that further researchers can explore the effectiveness of Quizwhizzer in different age groups or in collaborative learning and different materials.